Frontiers of modern asset allocation - Kaplan, Paul D. (Hoboken, N.J. : John Wiley & Sons, 2012)
'Through a series of articles spanning over 15 years of research, Paul D. Kaplan, who developed the methodologies behind the Morningstar Rating and the Morningstar Style Box tackles the issues investors face when they attempt to put the concepts of asset allocation into practice, among them: How should the asset classes be defined? Should equities be divided into asset classes based on investment style, geography, or other factors? Should asset classes be represented by market-cap-weighted indexes or should other principles, such as fundamental weights, be used? How do actively managed funds fit into asset-class mixes? Kaplan also interviews the intellectuals who have greatly influenced the evolution of asset allocation, including Harry Markowitz, Roger Ibbotson, and the late Benoit Mandelbrot. Throughout the book, Kaplan offers his own opinions and analysis. He includes three appendices that put theory into action with technical details for new asset-allocation frameworks, including the next generation of portfolio construction, which Kaplan dubs'Markowitz 2.0.''--
Includes bibliographical references and index.
Keywords: Portfolio management; Investments